Electronic Voting: 7th International Joint Conference, E-Vote-ID 2022, Bregenz, Austria, October 4–7, 2022, Proceedings - Krimmer, Robert; Volkamer, Melanie; Duenas-Cid, David; Rønne, Peter; Germann, Micha (Lecture Notes in Computer Science, 2022)
This open access book LNCS 13353 constitutes the proceedings of the 7th International Conference on Electronic Voting, E-Vote-ID 2022, held in Bregenz, Austria, in October 2022. The 10 full papers presented were carefully reviewed and selected from 39 submissions. The conference collected the most relevant debates on the development of Electronic Voting, from aspects relating to security and usability through to practical experiences and applications of voting systems, also including legal, social, or political aspects, amongst others.